Masked polycythemia vera diagnosed according to WHO and BCSH classification. Issue 2 (February 2014) - Barbui, Tiziano; Thiele, Jürgen; Carobbio, Alessandra; Gisslinger, Heinz; Finazzi, Guido; Rumi, Elisa; Luigia Randi, Maria; Vannucchi, Alessandro M.; Gisslinger, Bettina; Müllauer, Leonhard; Ruggeri, Marco; Rambaldi, Alessandro; et al.
<x xml:space="preserve">Abstract</x> Polycythemia vera (PV) is currently diagnosed by the World Health Organization (WHO) criteria regarding hemoglobin (HB) levels and JAK2V617F and related mutations or by the British Committee for Standards in Haematology (BCSH) guidelines predominantly based on hematocrit (HCT) values (>52% in men and >48% in women) in JAK2 mutated patients. We examined clinical features at diagnosis and outcome in 397 mutated PV patients showing a bone marrow (BM) morphology conforming with the WHO descriptions but including also cases with a HB level <18.5 g/dL in males (range 16.0–18.4) and <16.5 g/dL in females (range 15.0–16.4). These patients were regarded as masked PV (mPV) comprising 140 (35%) cases of our cohort. A comparison with the BCSH criteria based on HCT levels revealed a decrease of mPV patients to 59 (15%). In both classification systems, mPV patients were more males, presented more frequently with higher platelet counts, and increased BM reticulin fibrosis. A worsening of overall survival was documented in mPV patients in comparison with overt PV following the WHO (P = 0.011) as well as the BCSH (P = 0.0019) criteria. Risk factors for inferior survival in mPV were age >65 years and white blood cell count >15 × 109/L. Without these risk factors mPV patients had the same survival as overt PV suggesting that a fraction of patients with HB lower than that required for WHO diagnosis should still be considered as overt PV. This study has established the existence of mPV by two different classification systems based on either HB or HCT threshold values. Am. J. Hematol. 89:199–202, 2014. © 2013 Wiley Periodicals, Inc.